Dynamics of emotion, problem solving, and identity: Portraits of three girl coders. Issue 3 (2nd July 2020) - Dahn, Maggie; DeLiema, David
ABSTRACT: Background and Context: Women are underrepresented in the field of computer science, a trend that in part can be traced to girls' early experiences with the discipline. Objective: Our aim is to show how three girls who became strong coders talked about their debugging practice at the intersection of problem solving, emotion, and identity. Method: We use the portraiture methodology to trace the goodness of a designed programming workshop environment. We aim to show the trajectories of three strong coders over the course of two years of participation in weekend and summer workshops. Findings: We found that creative reflection spaces through journaling, art making, and storytelling opened possibilities for the learners to observe, understand, and critically examine the integration between problem solving, emotion, and identity in their programming experience. Implications: Findings have implications for designing inclusive programming learning environments that invite collective reflection on the moment-to-moment experience of learning to code.